Implementation of Government Regulation on Civil Servant Discipline at the Regional Secretariat of North Sulawesi Province - Yonathan Barambula; Muh. Ilham; Eva Eviany (INFOKUM, 2025)
This study discusses the problems in the implementation of Government Regulation Number 94 of 2021 concerning Civil Servant Discipline at the Regional Secretariat of North Sulawesi Province. Although this policy aims to strengthen the culture of ASN discipline, in its implementation there are still obstacles that have an impact on its effectiveness. The focus of the research is directed at the Implementation of Government Regulations on Civil Servant Discipline at the Regional Secretariat of North Sulawesi Province. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through in-depth interviews, observations, and documentation studies. Data analysis is carried out interactively using the Van Meter and Van Horn policy implementation theory, which includes six main variables: policy standards and targets, resources, characteristics of implementing agents, inter-organizational communication, socio-political environmental conditions, and implementer dispositions. The results of the study indicate that the implementation of the civil servant discipline policy has not been fully optimal. Some of the obstacles found include the lack of employee understanding of the contents of the regulations, limitations in terms of policy socialization, budget limitations, and the suboptimal supporting facilities and infrastructure. In addition, communication between work units is not yet fully consistent, which has an impact on the coordination of policy implementation. The conclusion of this study is that the implementation of Government Regulation Number 94 of 2021 still needs to be strengthened through increasing human resource capacity, ongoing socialization, and consistent supervision. The researcher recommends improvements in aspects of internal communication, budget allocation for disciplinary enforcement activities, and the use of information technology to support effective policy implementation.